The Dentition: A Complex System Demonstrating Self- Principles - Brook, A.; O'Donnell, M. B. (2011 IEEE Fifth International Conference on Self-Adaptive and Self-Organizing Systems, 2011)
Valuable research, clinical and teaching outcomes can develop from investigating the dentition as a complex system exhibiting self-adaptive and self-organizing (SASO) principles. As a basis for these investigations substantial amounts of hard data have been obtained and collated concerning the molecular, cellular and macroscopic levels of the development of the dentition in different species. The use of customized 2D image analysis and 3D laser scanning has provided accurate measurement data of the mature dentition. The aims of this paper are first to examine this information against the recognized general characteristics of complex systems to evaluate whether future computational studies are indicated and second how the novel modeling of dental morphology as a complex SASO system offers principles, processes and structures applicable to networks, services and engineering systems.